PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL STRUCTURED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATERI FLUIDA STATIS - Rohmah Primadani; Tukiran Tukiran; Budi Jatmiko (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
Curriculum 2013 emphasizes learning not only the achievement of knowledge, but also emphasizes the skills of students by providing sufficient  space for students to develop their creativity and independence so that it has the ability to think logical, critical, creative thinkings  and have problem solving skills. The lack of students skill in problem solving may be caused partly because of the lack of teaching materials that are specifically designed to enhance students skill in problem solving. Therefore in this study it is developed a physics teaching materials based on structured inquiry model as an effort to improve students skill in problem solving. Development of the teaching materials used 4D models and tried out at class X  SMAN 1 Krian in 2014/2015. The materials are tried out using One Group Pre-test and post-test design. Data collection methods was conducted using validation, testing, observation, and questionnaires. Data analysis technique was conducted using quantitative and qualitative descriptive. Based on the data analysis and discussion, it is obtained: 1) teaching materials developed is  classified as valid; 2) book and students worksheet readability has a high category; 3) the implementation of lesson plans is performed well, although there are still several problems (time for managing class and the difficulty is using equipments); 4) dominant activity  of students is to implement problem-solving plan; 5) problem solving skills of students after learning increases significantly with high category; and 6) the students response to the learning model of structured inquiry is classified as positive. Based on the data analysis and discussion, it can be concluded that the developed teaching materials was feasible to be used in learning process to improve students skill in problem-solving for static fluid. Kurikulum 2013 menekankan pembelajaran selain pada pencapaian pengetahuan, juga menekankan pada keterampilan siswa dengan memberi ruang yang cukup bagi siswa untuk mengembangkan kreativitas dan kemandirian mereka sehingga memiliki kemampuan berpikir logis, kritis, dan kreatif serta memiliki keterampilan pemecahan masalah. Kurangnya keterampilan pemecahan masalah siswa dapat disebabkan antara lain karena belum adanya perangkat pembelajaran yang khusus dirancang untuk meningkatkan keterampilan pemecahan masalah siswa. Untuk itu dalam penelitian ini dikembangkan perangkat pembelajaran fisika model structured inquiry sebagai usaha meningkatkan keterampilan pemecahan masalah siswa. Pengembangan perangkat  pembelajaran menggunakan model 4D dan diujicobakan pada siswa kelas X di SMAN 1 Krian pada semester genap tahun pelajaran 2014/2015. Desain ujicoba perangkat menggunakan One Group Pre-test and Post-test Design. Metode pengumpulan data yang digunakan adalah validasi, tes, observasi, dan angket. Sedangkan teknik analisis data menggunakan analisis deskriptif kuantitatif dan deskriptif kualitatif. Berdasarkan analisis dan pembahasan diperoleh beberapa temuan, yaitu: 1) perangkat pembelajaran yang dikembangkan tergolong valid; 2) keterbacaan BAS dan LKS tergolong tinggi; 3) pada pelaksanaan ujicoba diperoleh RPP terlaksana dengan baik, meskipun masih ada beberapa kendala (waktu untuk mengelola kelas dan kesulitan dalam menggunakan alat ukur); 4) aktivitas siswa yang dominan adalah melaksanakan rencana pemecahan masalah; 5) keterampilan pemecahan masalah siswa setelah pembelajaran  meningkat signifikan dengan kategori tinggi; dan 6) respon siswa terhadap pembelajaran model structured inquiry tergolong positif. Berdasarkan hasil analisis dan diskusi penelitian dapat disimpulkan bahwa perangkat pembelajaran yang dikembangkan mempunyai kualitas yang layak digunakan dalam pembelajaran untuk meningkatkan keterampilan pemecahan masalah siswa pada materi fluida statis.